Assessment of rural energy use and potential in Myanmar - Thi Thi Aye; Heredia , J.B.; Bhattacharya, Sribas C.; Giap, Van Dang; Kumar, Sivanappan; French Government (Bangkok : Asian Institute of Technology, 1995)
The pattern of the rural energy use in Myanmar has been studied. In order to get the consumption pattern of the rural area, the survey has been conducted in three villages: one represents the hilly region, one represents the coastal region and one represents the dry zone as Myanmar has the three main regions. The potential energy sources of the each region are assessed from the discussion and information passed though the energy institutional organizations. Finally, the marginal costs for the potential energy sources are set up at the current production level. The fuelwood consumption is predominant in rural area and it accounts for 69.8% of the total energy use. The consumption pattern in rural area has been changing since the economy became market oriented system in 1989. Hydropower, biomass, natural gas and coal are high potential in Myanmar. However, the overcutting of fuelwood causes deforestation in a certain places. Although solar and wind energy are non conventional energy, the data for some places shows the high potential. The results from the marginal costs show that rice husk, fuelwood, coal and hydroelectricity are attractive to develop. Solar and wind energy are attractive to install the small scale power system.
A thesis progress report submitted in partial fulfillment of the requirement for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1995
Keywords: Energy consumption -- Myanmar